Assessing the Impact of Early Childhood Education on the Community - Precious Aza (Uganda Christian University, 2024)
This study was carried out in to assess the impacts of early childhood education on the community, the researcher used various research articles on early childhood education and used research questions to find answers to the topic. The study also reviewed various literatures on early childhood education programs, benefits and impacts not leaving the ministry of education and sports, talked about the national curriculum for early childhood education as well. The research objectives included the social and economic benefits of early childhood education on the community and contribution of early childhood education towards the child’s academic performance. The researcher also used the qualitative research design structure of content analysis to analyze the findings. The study also revealed that the early childhood education has positively impacted on the community and the learners, which is possible with the presence of stakeholders such as school superiors, government, community members and parents. The findings also reveal that learners find it easy to transition into primary school. They gain cognitive and social skills hence are social with others in the community, it’s also a source of capital to the community members. Therefore, its recommended that private and government authorizes including parents should invest and work together in the early childhood education sector to see good outcomes in the community. In conclusion, the impact of early childhood education on the community is beneficial to the whole country .
Undergraduate Research